Intraoperative cell salvage with autologous transfusion in liver transplantation - Pinto, Marcelo A (World J Gastrointest Surg, 2019)
Liver transplant (LT) is the primary treatment for patients with end-stage liver disease. About 25000 LTs are performed annually in the world. The potential for intraoperative bleeding is quite variable. However, massive bleeding is common and requires blood transfusion. Allogeneic blood transfusion has an immunosuppressive effect and an impact on recipient survival, in addition to the risk of transmission of viral infections and transfusion errors, among others. Techniques to prevent excessive bleeding or to use autologous blood have been proposed to minimize the negative effects of allogeneic blood transfusion. Intraoperative reinfusion of autologous blood is possible through previous self-donation or blood collected during the operation. However, LT does not normally allow autologous transfusion by prior self-donation. Hence, using autologous blood collected intraoperatively is the most feasible option. The use of intraoperative blood salvage autotransfusion (IBSA) minimizes the perioperative use of allogeneic blood, preventing negative transfusion effects without negatively impacting other clinical outcomes. The use of IBSA in patients with cancer is still a matter of debate due to the theoretical risk of reinfusion of tumor cells. However, studies have demonstrated the safety of IBSA in several surgical procedures, including LT for hepatocellular carcinoma. Considering the literature available to date, we can state that IBSA should be routinely used in LT, both in patients with cancer and in patients with benign diseases.